Success in exporting : evidence from U.S. small- and medium-size companies' international strategies in recent years - Movassaghi, Hormoz ([s.n.] [S.l.], 1994)
Examines the export behaviour of selected firms who had received the 'E or 'E Star' awards, profiled in the Journal of Commerce and those received by Business America for their success in exporting.